2020
DOI: 10.1111/1440-1681.13240
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hydrogen sulphide on oxidative stress, inflammatory cytokines, and vascular remodelling in l‐NAME‐induced hypertension

Abstract: This study was designed to evaluate the protective effects of hydrogen sulphide (H2S) against NG‐Nitro l‐Arginine Methyl Ester (l‐NAME)‐induced hypertension and its possible effects on the inflammatory process, oxidative stress, and vascular remodelling in rats. Forty male Wistar Albino rats were assigned to four equal groups: the control group, the H2S control group, the hypertensive group, and the treated group, which received concomitant treatment with sodium hydrosulphide (NaHS) and l‐NAME. Systolic blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 40 publications
(83 reference statements)
0
3
0
Order By: Relevance
“…As previously established, the limited availability of oxygen during hypoxia forces cells to rely on less efficient metabolic routes such as glycolysis for ATP production [ 47 , 48 ]. Nonetheless, previous reports in our laboratory and others suggest that H 2 S donors enhance mitochondrial bioenergetics [ 37 , 46 , 87 ] and modulate anti-oxidant [ 87 ] and anti-inflammatory processes in the vascular system [ 26 , 40 , 88 , 89 ], potentially by acting as an electron donor to the electron transport chain [ 90 ]. Figure 5 and Figure 6 highlight that non-encapsulated and liposome formulated STS significantly enhanced rates of mitochondrial respiration in cells challenged with hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…As previously established, the limited availability of oxygen during hypoxia forces cells to rely on less efficient metabolic routes such as glycolysis for ATP production [ 47 , 48 ]. Nonetheless, previous reports in our laboratory and others suggest that H 2 S donors enhance mitochondrial bioenergetics [ 37 , 46 , 87 ] and modulate anti-oxidant [ 87 ] and anti-inflammatory processes in the vascular system [ 26 , 40 , 88 , 89 ], potentially by acting as an electron donor to the electron transport chain [ 90 ]. Figure 5 and Figure 6 highlight that non-encapsulated and liposome formulated STS significantly enhanced rates of mitochondrial respiration in cells challenged with hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…Although a large number of studies have reported the regulatory role of H 2 S in both pro-and anti-inflammatory processes, the mechanistic insights of H 2 S in inflammatory processes are still unclear. [154][155][156][157] Zanardo et al reported that H 2 S can induce neutrophil apoptosis and inhibit the expression of some leukocytes and endothelial adhesion molecules by activating K ATP channels to suppress endogenous H 2 S production and elicit leukocyte adherence. [158] Ekundi-Valentim et al reported that exogenous H 2 S achieved a prominent anti-inflammatory and antinociceptive effect when delivered to the knee joint, while H 2 S produced in situ exerted weak immunomodulatory effect.…”
Section: Anti-inflammationmentioning
confidence: 99%
“…[213] In summary, although the intrinsic mechanism of H 2 S antioxidant defense response is disputable, it is possible that the production and bioavailability of H 2 S can directly regulate cellular redox status for antioxidant effect. [154,155,214]…”
Section: Antioxidant Defense Responsementioning
confidence: 99%